Interplay of Investor Cognition, Financial Literacy, and Neuroplasticity in Investment Decision Making: A Study of Nepalese Investors - Nepal, Rachana; Rajopadhyay, Pradeep; Rajopadhyay, Umesh; Bhattarai, Ujjwal (Journal of Business and Social Sciences Research, 2023)
The study examines how investor cognition and financial literacy impact neuroplasticity among Nepalese investors in stock market by assessing the mediating effect of risk absorption capacity in relation to investor cognition, financial literacy and neuroplasticity in investors. The cross-sectional data was purposefully collected from 389 respondents ranging from under 25 years to older residing in the Kathmandu valley and had previously invested in market and incurred losses. Primary data was analysed quantitatively by using SMARTPLS. The study findings indicated significant impacts of the constructs - investors’ cognition, financial literacy, and risk absorption, on investors’ neuroplasticity. Additionally, the structural model affirms that risk absorption acts as a mediator in the relationship between investors’ cognition, financial literacy, and neuroplasticity. By filling in empirical gaps and utilising social cognitive theory, this study advances our knowledge of how investor cognition, financial literacy, risk absorption capacity, and neuroplasticity impacts financial decisions, especially in developing countries like Nepal. Thus, this study stresses the eminent role of cognitive processes and financial literacy in decision-making, with the potential to assist policy formulation for equity-related financial product marketers and aid in tackling psychological trauma and reluctance among prospective investors in stock markets due to past losses.